2019
DOI: 10.1155/2019/3548396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immunomodulatory Supplements Based on Echinacea Angustifolia and Echinacea Purpurea on the Posttreatment Relapse Incidence of Genital Condylomatosis: A Prospective Randomized Study

Abstract: Introduction. HPV infection is a highly infectious disease; about 65% of partners of individuals with genital warts will develop genital condylomatosis. Only in 20-30% it regresses spontaneously and relapse rates range deeply (9-80%). Echinacea extracts possess antiviral and immunomodulator activities. The aim of this study was to evaluate the efficacy of the therapy, using a formulation based on HPVADL18® (on dry extracts of 200 mg Echinacea Purpurea (EP) roots plus E. Angustifolia (EA)), on the posttreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…However, the efficacy was reduced in the case of extended condylomatosis, for which an increased relapse rate was reported. Such findings confirmed that EP and EA dry root extracts could be a valid adjuvant therapy to reduce the recurrence of genital condylomatosis [ 19 ].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the efficacy was reduced in the case of extended condylomatosis, for which an increased relapse rate was reported. Such findings confirmed that EP and EA dry root extracts could be a valid adjuvant therapy to reduce the recurrence of genital condylomatosis [ 19 ].…”
Section: Discussionsupporting
confidence: 65%
“…In a recent prospective study, De Rosa et al [ 19 ] showed that, in the case of HPV-related genital condylomatosis, the relapse incidence of visible warts was significantly lower with treatment with oral EP and EA and progressively decreases during the 12 months follow-up. The efficacy was for both men and women with visible condylomatosis.…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ (more than 3 times) less than E. purpurea requirement that indicates the need to NO 3 − fertilizers apply in order to increase NO 3 − level in the studied soil. Nitrate leaching from agricultural soils is common due to anionic nature of NO 3 − ion and non-adsorption on negatively charged soil exchangeable sites, which leads to apply of different N fertilizers to soil 7 . In present study, the soil N deficiency was calculated with regard to E. purpurea N-requirement and provided the optimum level of NO 3 − concentration for the plant growth by using different N fertilizers containing various percentages of NO 3 − .…”
Section: Discussionmentioning
confidence: 99%
“…Comparing of other Echinacea species, E. purpurea is the most able species to adjust to new conditions. It is resistance to heat or cold weather conditions, easy to grow, and flaunt high efficiency 7 , 8 . Numerous scientific researches demonstrated the useful effect of Echinacea immunomodulatory functions and human health 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Combination therapy, namely immunomodulatory agents including Echinacea, associated with better response rate and lower recurrences. Previous studies stated that Echinacea could be used as an immunomodulator in cases of genital warts and no recurrences were found [6]. Health professionals might consider Echinacea in high risk patient, recurrent lesions, multiple lesions, recalcitrant lesions, and difficult to treat areas [7].…”
Section: Introductionmentioning
confidence: 99%